Humoral immune response after COVID-19 in multiple sclerosis: A nation-wide Austrian study. (December 2021) - Bsteh, Gabriel; Dürauer, Sophie; Assar, Hamid; Hegen, Harald; Heschl, Bettina; Leutmezer, Fritz; Pauli, Franziska Di; Gradl, Christiane; Traxler, Gerhard; Zulehner, Gudrun; Rommer, Paulus; Wipfler, Peter; et al.
Background: Knowledge on immunity after SARS-CoV-2 infection in patients with multiple sclerosis (pwMS) and the impact of disease-modifying treatment (DMT) is limited. Objective: To evaluate degree, duration and potential predictors of specific humoral immune response in pwMS with prior COVID-19. Methods: Anti-SARS-CoV-2 antibody testing was performed in pwMS with PCR-confirmed diagnosis of symptomatic COVID-19 from a nation-wide registry. Predictors of seropositivity were identified by multivariate regression models. Results: In 125 pwMS (mean age = 42.4 years (SD = 12.3 years), 70% female), anti-SARS-CoV-2 antibodies were detected in 76.0% after a median of 5.2 months from positive PCR. Seropositivity rate was significantly lower in patients on IS-DMT (61.4%, p  = 0.001) than without DMT or immunomodulatory DMT (80.6%; 86.0%, respectively). In multivariate analysis, IS-DMT was associated with reduced probability of seropositivity (odds ratio (OR): 0.51; 95% confidence interval (95% CI): 0.17–0.82; p  < 0.001). Predefined subgroup analyses showed marked reduction of seropositivity in pwMS on rituximab/ocrelizumab (OR 0.15; 95% CI: 0.05–0.56; p  < 0.001). Rate of seropositivity did not change significantly over 6 months. Conclusions: Humoral immunity is stable after SARS-CoV-2 infection in MS, but is reduced by immunosuppressive DMT, particularly anti-CD20 monoclonal antibodies. This provides important evidence for advising pwMS as well as for planning and prioritizing vaccination.